Pengaruh Influencer Review Dan Kualitas Produk Terhadap Minat Pembelian Produk Skincare Skintific : Studi Kasus Di Universitas Bhayangkara Jakarta Raya - Novia Rahmawati; Widi Winarso; Kardinah Indrianna Meutia; Milda Handayani; Rini Wijayaningsih (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to research, test and assess the influence of the independent variables influencer reviews and product quality on the dependent variable interest in purchasing Skintific skincare products among female students at Bhayangkara University, Jakarta Raya. The sample for this research was 140 female students. This type of research uses a quantitative approach. Data was collected directly from respondents using research instruments in the form of questionnaires via Google Form and purposive sampling techniques. then the data results are processed using the SPSS 26 data processing application. The results of this research prove that influencer reviews and product quality have a positive and significant effect on.